Stigmatizing attitudes towards people living with HIV/ AIDS PLWHA among primary health care providers in Kinta District, Perak - Chan, Yuen Ching; Mawardi, Maliza; Ismail@Daud, Adibah Hanim (Academy of Family Physicians of Malysia, 2021)
Background: Stigmatizing attitudes expressed by health care providers prevent some members of at-risk populations from accessing human immunodeficiency virus (HIV) screening and care. This attitude contributes to the continuity of the infection dissemination within our community, which gives an impact on the healthcare service and the curtailment of the global HIV/acquired immunodeficiency syndrome (AIDS) pandemic. Objective: This study was conducted to identify stigmatizing attitudes toward people living with HIV/AIDS (PLWHA) and their determinants among primary health care providers in Kinta District, Perak. Methodology: A cross-sectional study was conducted in 36 primary care clinics in Kinta District, Perak. Using stratified random sampling, 365 primary health care providers were recruited into the study. A validated self-administered questionnaire was used to obtain sociodemographic data as well as information on the healthcare experiences of healthcare providers, their knowledge of HIV/AIDS, and attitudes toward PLWHA. Determinants were identified using multiple linear regression. Results: More than half of the respondents (54.1%) had never provided care to HIV/AIDS patients. A minority (29.9%) had received training on HIV/AIDS. This study shows that doctors (Coef.= -9.50, 95% CI: -18.93, -0.07, p= 0.048), respondents with HIV-positive relatives, (Coef.= -5.61, 95% CI: -10.57, -0.65, p= 0.027), those who had provided care to HIV/AIDS patients (Coef.= -2.38, 95% CI: -4.31, -0.45, p= 0.016), and those with a higher knowledge score on HIV/AIDS (Coef.= -0.86, 95% CI: -1.59, -0.13, p= 0.021) were less likely to show stigmatizing attitudes toward PLWHA. Conclusion: The issue of stigmatizing attitudes toward PLWHA among primary health care providers needs to be addressed. This study finds that knowledge, profession, experiences with caring for PLWHA, gender, and having HIV-positive relatives are significant predictors of stigmatizing attitudes toward PLWHA among primary health care providers in Kinta District, Perak. Interventional programs to improve knowledge and awareness, as well as decrease stigma toward PLWHA, should be implemented among all health care providers, especially those who have no opportunity to provide direct care.